THE DETERMINANTS OF NON-PERFORMING FINANCING OF SHARIA BANKING IN INDONESIA: THE STUDY OF META-ANALYSIS - Nabila Rifda Darmawanti; Noven Suprayogi (Jurnal Ekonomi Syariah Teori dan Terapan, 2020)
This study attempts to determine the factors influencing non-performing financing of Islamic Banks in Indonesia using samples from published journals in Indonesia for seven years (2012-2018). The purpose of this research is to examine the association between BOPO, GDP, inflation, FDR, CAR, FAR, SBIS, and bank size. This research applies the meta-analysis technique to samples of 17 articles. The articles used are selected studies from Sinta Journal, Garuda and Google Scholar. The research shows that BOPO, GDP, inflation, CAR, FAR, and bank size have significant correlation with non-performing financing of Islamic banks in Indonesia. Meanwhile, FDR and SBIS have no significant correlation with non-performing financing of Islamic banks in Indonesia.Keywords: non-performing financing, Islamic bank, journal article, meta-analysis.REFFERENCE Ahmed, K. (2013). A Meta-analysis of IFRS adoption effects. The International Journal of Accounting, 48(2), 173-217.Antonio, M.S. (2007). Bank syariah dari teori ke praktek. Jakarta: Gema Insani.Akbar, Dinnul Alfian. (2016). Inflasi, Gross Domestic Product (GDP), Capital Adequacy Ratio (CAR), Dan Financing to Deposit Ratio (FDR) Terhadap Non Performing Financing pada Bank Umum Syariah di Indonesia. I-Economics: A Research Journal on Islamic Economics, 2(2), 19-37.Asnaini, Sri Wahyuni. (2014). Faktor-faktor yang mempengaruhi Non Performing Financing (NPF) pada Bank Umum Syariah di Indonesia. Jurnal Telaah dan Akuntansi Bisnis (TEKUN), 5(2), 264-280.Auliani, Mia Maraya & Syaichu. (2016). Analisis pengaruh faktor internal dan faktor eksternal terhadap pembiayaan bermasalah pada bank umum syariah di Indonesia periode tahun 2010-2014. Diponegoro Journal of Management, 5(3), 1-14.Fanani, Zaenal. (2014). Karakteristik perusahaan dan corporate governance terhadap manajemen laba: studi analisis meta. Jurnal Keuangan dan Perbankan, 18(2), 181-200.Firmansari, Daisy & Noven Suprayogi. (2015). Pengaruh Variabel Makroekonomi Dan Variabel Spesifik Bank Terhadap Non Performing Financing Pada Bank Umum Syariah Dan Unit Usaha Syariah Di Indonesia Periode 2003-2014. Jurnal Ekonomi Syariah Teori dan Terapan, 2(6), 512-520.Firmansyah, Irman (2014). Determinant of Non Performing Loan: The case of Islamic bank in Indonesia. Buletin Ekonomi Moneter dan Perbankan, 17(2), 251-268.Hamzah, Amir (2018). Pengaruh faktor makro ekonomi terhadap pembiayaan bermasalah (penelitian pada bank umum syariah di Indonesia tahun 2010-2017. Journal of Islamic Financing and Accounting, 1(2).Hunter, J.E. & Schmidt, F.L. (2004). Methods of meta-analysis: correcting error and bias in research findings. Beverly Hills, CA: Sage Publications.Indiastary, Diyas. (2019). Meta-analisis: faktor-faktor yang mempengaruhi dana pihak ketiga perbankan syariah di Indonesia. Skripsi tidak diterbitkan. Surabaya: Fakultas Ekonomi dan Bisnis Universitas Airlangga.Mutamimah dan Siti Nur Zaidah Chasanah. (2012). Analisis eksternal dan internal dalam menentukan non performing financing bank umum syariah di Indonesia. Jurnal Bisnis dan Ekonomi (JBE), 19(1), 49-64.Rani, Lina Nugraha. (2013) Analisis faktor-faktor yang mempengaruhi Non Performing Financing (NPF) pada perbankan syariah di Indonesia. Tesis tidak diterbitkan. Surabaya: Program Pascasarjana Magister Sains Ekonomi Islam Universitas Airlangga.Rosidah, Euis. (2017). Pengaruh Financing To Deposit Ratio tehadap Non Performing Financing perbankan syariah di Indonesia. Jurnal Akuntansi, 12(2), 127-134.Siddiqui, S.S. (2015). The association between corporate governance and firm performance – a meta-analysis. International Journal of Accounting and Information Management, 23(3), 218-237.Singh, H.P, et al. (2017). Working capital management and firm profitability: a meta-analysis. Qualitative Research in Financial Markets, 9(1), 34-47.Solihatun. (2014). Analisis Non Performing Financing (NPF) Bank Umum Syariah Di Indonesia Tahun 2007-2012.Jurnal Ekonomi Pembangunan, 12(1), 57-68.Thiarany, Usy. (2017). Faktor-Faktor Yang Memengaruhi Non Performing Financing Pada Bank Umum Syariah. Skripsi tidak diterbitkan. Bogor: Institut Pertanian Bogor.Wibowo, S.A, dan Wahyu Saputra. (2017). Pengaruh Variabel Makro dan Mikro Ekonomi terhadap Pembiayaan Bermasalah pada Bank Syariah. Jurnal Ilmiah Akuntansi, 2(1), 96-112.Vanni, K.M., Wahibur Rokhman. (2017). Analisis Faktor-Faktor yang Mempengaruhi Non Performing Financing Pada Perbankan Syariah di Indonesia Tahun 2011-2016.EQUILIBRIUM: Jurnal Ekonomi Syariah, 5(2), 306-319.Yasin, A, Tika Widiastuti. (2014). Determinan Non Performing Financing Pada Industri Bank Pembiayaan Rakyat (BPR) Syariah di Indonesia. Jurnal Ekonomi, Manajemen, dan Akuntansi Islam Imanensi, 2(1), 1-11.